Cloning, expression, crystallization and preliminary X‐ray studies of a superfolder GFP fusion of cyanobacterial Psb32. Issue 4 (1st April 2015) - Liauw, Pasqual; Kannchen, Daniela; Gasper, Raphael; Dyczmons‐Nowaczyk, Nina; Nowaczyk, Marc M.; Hofmann, Eckhard
<x xml:space="preserve">Abstract</x> A fusion of Psb32 from the thermophilic cyanobacterium Thermosynechococcus elongatus BP‐1 (TePsb32) with superfolder GFP was created for enhanced solubility and improved detection and purification. The fusion protein readily formed large hexagonal crystals belonging to space group P6122. A full data set extending to 2.3 Å resolution was collected at the Swiss Light Source. The phase problem could be solved by using only the sfGFP fusion partner or by using GFP and AtTLP18.3 from Arabidopsis thaliana as search models. Based on this expression construct, a versatile library of 24 vectors combining four different superfolder GFP variants and three affinity tags was generated to facilitate expression and screening of fluorescent fusion proteins.